2021
DOI: 10.1186/s12888-021-03587-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical limitations and depressive symptoms among Indian elderly: marital status as a moderator

Abstract: Background Depression among the elderly is well-documented and associated with socio-economic factors, physical and mental health conditions. Few studies have focused on older adults’ physical limitations and depressive symptoms. However, very little is known about marital status’ role in such associations, especially in India. The present study examines the association between physical limitations and self-reported depressive symptoms and moderating role of marital status in such association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
(48 reference statements)
5
24
1
Order By: Relevance
“…A community level study on primary care population in India estimated high prevalence of multimorbidity among older adults, women and individuals of high socioeconomic status, and significant gender differences in prevalence of multimorbidity have been reported [ 42 , 43 ]. While a study by Hossain et al (2021) have explored the association between physical limitations and self-reported depressive symptoms among Indian older adults considering marital status as a moderator in such association [ 44 ]. However, despite the fact that there is an increased chance of depression in older persons as the number of chronic illnesses or multimorbidity grows, the underlying route or mechanism explaining the multimorbidity-depression association remains unexplained in the Indian context.…”
Section: Introductionmentioning
confidence: 99%
“…A community level study on primary care population in India estimated high prevalence of multimorbidity among older adults, women and individuals of high socioeconomic status, and significant gender differences in prevalence of multimorbidity have been reported [ 42 , 43 ]. While a study by Hossain et al (2021) have explored the association between physical limitations and self-reported depressive symptoms among Indian older adults considering marital status as a moderator in such association [ 44 ]. However, despite the fact that there is an increased chance of depression in older persons as the number of chronic illnesses or multimorbidity grows, the underlying route or mechanism explaining the multimorbidity-depression association remains unexplained in the Indian context.…”
Section: Introductionmentioning
confidence: 99%
“…Marriage, it is assumed, strengthens social support, and wealth and prevents risky behaviour, leading to improved health. As a result, several studies have also reported that married people have lower mortality rates [ 11 , 12 ], longer life expectancy [ 13 , 14 ], fewer physical health problems [ 15 , 16 ], are protected from life stresses and depression [ 17 , 18 ], and shorter hospital stays, lower chance of nursing home admission as well as better quality health care use [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India, where male dominance continues to exist, the culture is highly normative, patrilineal, and patriarchal [ 47 – 49 ]. Previous research has demonstrated that gender inequalities in marriage and health outcomes strongly persist [ 18 , 20 , 50 – 53 ]. At the same time, several studies have focused on self-reported health and marital status in India.…”
Section: Introductionmentioning
confidence: 99%
“…In older adult, the spouse helps their spouse with physical limitations and provides the most of the assistance and care [ 81 ]. With the help of their wives, married men with functional limitations saw a decrease in their depressive symptoms, but the relationship was lost for women [ 82 ]. The unmarried elderly typically experience longer periods of loneliness and lack of social support, which makes them more prone to depression [ 83 ].…”
Section: Discussionmentioning
confidence: 99%